2016
DOI: 10.21608/bvmj.2016.31402
|View full text |Cite
|
Sign up to set email alerts
|

Detection of some foodborne pathogens in meat products by Polymerase Chain Reaction

Abstract: A total of 100 random samples of meat products including raw minced meat, raw sausage, luncheon and basterma (25 samples of each) were collected from different markets in Cairo and Giza governorates to be examined bacteriologically for detection of Staphylococcus aureus, Listeria monocytogenes and Escherichia coli. These samples were examined for isolation of such pathogens by conventional bacteriological methods and by polymerase chain reaction (PCR). Concerning S.aureus bacteriological results revealed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Results in Table 1 revealed that L. monocytogenes was detected in minced meat with percentage of 4.6%. Nearly similar results were reported by Armany et al, 2016 Higher results were mentioned by Kalender, 2012 andAbdeen et al, 2021 who detected L. monocytogenes in a percentage of 7.2% and 14%, respectively. Contamination of minced meat by L. monocytogenes may be occurs during animals slaughtering, transportation, workers hands and equipment used such as mincing machine, knifes, and packaging tools.…”
Section: Discussionsupporting
confidence: 84%
“…Results in Table 1 revealed that L. monocytogenes was detected in minced meat with percentage of 4.6%. Nearly similar results were reported by Armany et al, 2016 Higher results were mentioned by Kalender, 2012 andAbdeen et al, 2021 who detected L. monocytogenes in a percentage of 7.2% and 14%, respectively. Contamination of minced meat by L. monocytogenes may be occurs during animals slaughtering, transportation, workers hands and equipment used such as mincing machine, knifes, and packaging tools.…”
Section: Discussionsupporting
confidence: 84%
“…The results of bacteriological examination of examined samples ( Table, 3) revealed that E. coli were isolated from, kofta, sausage samples (8.6% for each), fresh meat, beef burger samples (5.7% for each) and luncheon (2.9%). Nearly similar results were obtained by Abd El-Salam-Azza (2014); Armany et al (2016) ; Tarabees et al (2015) and El-Rais, Eman(2018).Meanwhile, these results were disagreed with those of Phillips et al ; Adwan et al (2015) and Ramadan (2015) who isolated E. coli from raw meat and meat products with high incidence. In addition, the results were disagreed with Wehab and Hegazy (2007) who could not isolate E. coli from beef burger samples with Siriken et al (2006) who failed to isolate E. coli from beef sausage samples.…”
Section: Discussionmentioning
confidence: 55%
“…aureus. as showed in Fig 1 . The results showed that PCR is an allegorical method for identification of foodborne pathogens, as it was more impressive, more sensitive, less labour, reduces time and effort after using gradient PCR in validation of every microbe (Armany et al 2016). Lanes 1, 2,3,4,5 (fresh meat) 6, 7, 8,9,10 (frozen meat)…”
Section: )mentioning
confidence: 99%